Examining the Joint Effects of Air Quality, Socioeconomic Factors on Indonesian Health - Ahmad Wijaya Kusuma; Yuwan Jumaryadi; Samidi; Richard; Anandha Fitriani (Aptisi Transactions On Technopreneurship (ATT), 2023)
Â This study addresses the pressing need to comprehensively manage air pollution by examining the roles of local and national public agencies from the perspective of the general public. Air quality poses a critical challenge that profoundly impacts various aspects of human life. To enhance our understanding and generate both theoretical and practical insights for public management, this research introduces several key variables: the engagement of authorities in mitigating air pollution, citizen involvement in pollution reduction efforts, financial incentives for individuals and businesses to adopt air-friendly behaviors, urban green investments, the communal consequences of air pollution, and the necessity for industrial participation. Employing Partial Least Squares Structural Equation Modeling (PLS-SEM) as the research approach, data was gathered from residents of Indonesia's largest cities, where pollution significantly affects society and governing bodies. The findings are pertinent for public managers at both local and national levels, providing valuable input to enhance strategies for curbing air pollution, enhancing air quality, and ultimately improving the well-being of inhabitants.